IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT IN IMPROVING STUDENT PERFORMANCE - Amaludin Bahansubu (Adisam Publisher, 2025)
The implementation of School-Based Management (SBM) is an administrative strategy that gives schools greater autonomy in the management of their own resources, with active participation from teachers, parents, and the community. The main objective of SBM is to improve the quality and effectiveness of the educational process, which ultimately aims to improve student performance. By giving schools greater authority and responsibility, it is expected to create a learning environment that is more responsive and suited to local needs. This research shows that effective implementation of SBM can increase the involvement of various stakeholders in decision-making and oversight of the teaching and learning process. The end result of this strategy is increased student motivation and academic achievement, along with the availability of more optimised and quality resources.